Sistem Informasi Pemesananan Tiket Tour And Travel Berbasis Website Menggunakan Metode Waterfall Pada Camelia Travel - Muhtajuddin Danny; Daimin Daimin (Jurnal SIGMA, 2022)
Camelia Travel is a tour and travel service provider company that has obstacles in running its business such as in the reservation process or ticket booking where customers in making ticket booking transactions cannot be done online, making it difficult for customers who are far from the location in ordering travel tickets. The purpose of this study is to create an information system that can provide convenience to consumers in booking travel tickets and facilitate Camelia Travel in managing reservation data or booking tour packages. The method used in this research is the waterfall method. The final result of this research is to produce a website-based tour package booking information system that can be a solution to the problems found in Camelia Travel such as providing convenience to Camelia Travel in managing business data and promoting tour packages and making it easier for consumers who are far from the location to do business data. ticket purchase reservation. Keyword: Tour and travel information system, website information system using the waterfall method